PERSEPSI PENGGUNA SHOPEE MENGENAI MANFAAT REVIEW DAN RATING PADA PRODUK CARGLOSS - Naswa Ika Febrianty; Aisya Ayuni Astutik; Lulu Nazma Lailatul Muchlis; Edita Rachma Kamila (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Shopee users' perceptions of reviews and ratings on Cargloss products are important in the process of choosing what to buy on online shopping sites. The issue discussed focuses on how users understand and use reviews and ratings as a source of information before purchasing car care products. The purpose of this paper is to assess the role of reviews and ratings in shaping users' views, trust, and confidence in Cargloss products on Shopee. The method employed is a literature review and conceptual analysis of various scientific sources on consumer behavior and e-commerce. The results of the discussion show that reviews are seen as a reflection of the genuine experiences of other users, providing qualitative information about product quality, while ratings function as quantitative indicators for consumers' initial assessments. The combination of reviews and ratings encourages users to be more selective and rational, and increases their trust in the products and sellers on Shopee. Keywords : User Perception, Product Reviews, Product Ratings, E-Commerce, Shopee